2021
DOI: 10.1186/s13018-021-02467-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific instrumentation combined with a new tool for gap balancing is useful in total knee replacement: a 3-year follow-up of a retrospective study

Abstract: Objective The purpose of this study was to determine whether the gap-balancing technique with patient-specific instrumentation (PSI) and a new balancing device in total knee arthroplasty (TKA) can improve knee function to a greater extent than can the measured resection technique. Materials and methods Data from 150 patients who underwent TKA from August 2014 to June 2016 were studied retrospectively. The gap-balancing technique assisted by PSI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…They found no significant differences in the functional scores or the proportion of patients between the gap balancing and measured resection groups who were satisfied at 6-month or 2-year post-surgery. Similar results were also reported by Deng et al [ 27 ]. They conducted a retrospective study and concluded that gap balancing performed with a new balancing device and PSI could produce accurate femoral component alignment as well as outcomes similar to those of the measured resection technique at 3 years.…”
Section: Discussionsupporting
confidence: 92%
“…They found no significant differences in the functional scores or the proportion of patients between the gap balancing and measured resection groups who were satisfied at 6-month or 2-year post-surgery. Similar results were also reported by Deng et al [ 27 ]. They conducted a retrospective study and concluded that gap balancing performed with a new balancing device and PSI could produce accurate femoral component alignment as well as outcomes similar to those of the measured resection technique at 3 years.…”
Section: Discussionsupporting
confidence: 92%